Islam dan Philosophia Perennis: Catatan atas Kritik Legenhausen Terhadap Philosophia Perennis Seyyed Hossein Nasr - Mulyani (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2018)
The idea of Philosophia Perrennis Seyyed Hossein Nasr isn’t detached from points of weakness, so Legenhausen gives critical notes on the Nasr thoughts. But, Legenhausen’s critical note also isn’t free from weakness too, so as its consequences, the public saw his critical notes is just defensively apologetic criticism of the Muslim orthodoxy. This paper tried to elaborate Legenhausen’s critical view, so that orthodoxy of traditional Islam is still authoritative.